Static Analysis at GitHub: An experience report. - CLEM, TIMOTHY; THOMSON, PATRICK (Communications of the ACM, 2022)
The article discusses computer code-navigation and hosting for the website github.com, operated by the firm GitHub, particularly focusing upon the static analysis stage that enables the extraction of name-binding information from source code. It examines the core ideas of the GitHub Semantic Code team including zero configuration, incrementality, and human partnering. The article also discusses the Ruby on Rails application codebase.